Efektivitas Penggunaan Helm Saat Berkendara di Wilayah Hukum Polres Bangli - I Komang Pande Rayana; I Ketut Sukadana; I Nyoman Sutama (Fakultas Hukum Universitas Warmadewa, 2019)
The use of Indonesian National Standard Helmets is very important in driving, because using a helmet, the failure due to an accident in driving can be minimized, and protect the head from the impact of hard objects when an accident occurs while driving. Communities sometimes do not understand the benefits of using helmets, so they seem to wear helmets for fear of police officers. The problem is how is Community Effectiveness in the use of Helmets when driving? And what are the efforts of the police in overcoming the low use of helmets when driving in the jurisdiction of the Bangli police station? The type of research used in this study is an empirical study; with the problem approach used in this research is juridical sociology. The source of the data comes from Primary and Secondary data, this research technique in data collection is done by means of interviews (interviews), and also Literature Studies. In this study the analysis carried out was quantitative analysis. The regulation of helmet use has been regulated in Article 106 paragraph (8) of Law Number 22 Year 2009, affirming the obligation to use Helmets which are the Indonesian National Standard (SNI). Based on the number of helmet use violations occurring within a period of 4 (four) years, public awareness in using helmets when driving can be said to be quite low, this is based on data that helmet use violations that occur in the Legal District of Bangli Police are still high. There are several factors that cause motorists to not use helmets; they are ignorance, lack of awareness and others. Police efforts in overcoming the low use of helmets are preventive measures such as socialization, while repressive efforts in the form of tickets to get the deterrent effect on the results of traffic violations.